Accept and value each person - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit Pub., 2006)
A young girl learns to recognize and appreciate the uniqueness qualities of the world's different people.
Book Links (A.L.A.)
2.1
K-3
K-3
Keywords: Individual differences -- Juvenile literature; Toleration -- Juvenile literature; Individual differences; Toleration; Individualism; Toleration